GARAP DAN STRUKTUR TARI ANOMAN CAKIL SUSUNAN DIDIK BAMBANG WAHYUDI - Nur Aini; Soemaryatmi Soemaryatmi (Institut Seni Indonesia Surakarta, 2020)
Anoman Cakil dance was created in 1986 at the request of the ASKI Dance Department. External factors are a major factor in the creation of Anoman Cakil dance which is supported by internal factors. This thesis, titled Anoman Cakil dance, composed by Didik Bambang Wahyudi, focuses on the study of dance work and the structural analysis of Anoman Cakil dance. Issues to be explained in this study are (1) How to work on Anoman Cakil dance by Didik Bambang Wahyudi (2) How to present the structure of Anoman Cakil dance.This research uses qualitative research methods, data obtained through literature study, interviews and observations. The results of data processing are then presented descriptively. To answer this problem, this study uses the concept of cultivation as a knife for analysis, namely the concept of cultivation by Rahayu Supanggah. The structural analysis of Sumandiyo Hadi was used as a theory to examine the structural problem of Anoman Cakil's dance presentation. The elements of cultivation work in the form of material work on, work on, working on facilities, working on furniture and determinant work on. Application of cultivation in dance in the form of the background of the creation of dance, Didik Bambang wahyudi as cultivators and Anoman cakil dance as material and means of working on.Anoman Cakil dance including wireng pethilan dance with stories originating from the Ramayana Epic, presented by two dancers in pairs, with figures Anoman and Cakil. And, victory on the Cakil figure. Anoman Cakil dance consists of three parts in the form of Forward Beksan Structure, the Beksan section which consists of the then spread hand arm and keris shell. Beksan retreat is the last part of the Anoman Cakil dance presentation structure. Dramatic flow of Anoman Cakil dance is classified as multiple conical dramatic grooves with a small climax before heading to the main climax. Keywords: Wireng, pethilan, Anoman, Work on, Structural.